Hypermobile spleen in congenital diaphragmatic hernia. Prevention and correction of complications - D.Y. Kryvchenia; V.P. Prytula; E.O. Rudenko; S.F. Hussaini; I.I. Shulzhyk (Group of Companies Med Expert, LLC, Kyev, Ukraine, 2020)
Hypermobile or wandering spleen is a rare pathology caused by weakness or an absence of supporting ligaments of the spleen. There are known asymptomatic clinical presentations and presence of the symptoms is associated with a torsion of the pedicle or compression of other organs. In the recent review of all cases of wandering spleen revealed single cases of mobile spleen associated with congenital diaphragmatic hernia (CDH) and some complications without emphasis on their prevention. Purpose - optimization of medical tactics in children with CDH taking into account the presence of a mobile spleen. Materials and methods. A retrospective analysis of surgical correction of CDH in 123 children undergoing treatment at the NCSH «OKHMATDYT» during 2009-2019 was conducted. The study included 6 patients who showed signs of a mobile spleen during surgery for left-sided CDH correction, or who had complications associated with this anomaly during the postoperative period. Mobile spleen and its complications were identified by ultrasound, upper esophagogastrial contrast study, intraoperative revision, and gallbladder and choledochal duct contrast study. Results and discussion. In this study group of patients, 4 (66.7%) patients were diagnosed with a mobile spleen during primary surgery, and 2 (33.3%) were diagnosed on the basis of clinical symptoms that developed after correction of CDH. Complications of the hypermobile spleen in our patients were as follows: obstruction of the stomach and external biliary tract, which were clinically manifested by symptoms such as mechanical icterus, spitting up and vomiting. The lengthening of the gastro-splenic ligament to 4-6 cm, the absence or lengthening of the spleno-diaphragmatic ligament to 4-5 cm, the absence of the splenic-renal ligament were revealed. Splenopexy was performed as a simultaneous operation during correction of diaphragmatic hernia (n=4) or as a second operation (n=2) to eliminate the complications of the vagus spleen. There was no need for repeated surgical interventions in these patients. Conclusions. CDH is a multicomponent malformation and the mobile spleen is an integral part of it. Increased mobility of the spleen after correction of CDH can be the cause of such complications as torsion and infarction of the spleen, compression and deformation of the stomach with gastroesophageal reflux, compression of the external biliary tract with their extension and simulation of the choledochal cyst, etc. Therefore, verification and correction of the mobile spleen during CDH repair should become a necessary element of surgical tactics. The research was carried out in accordance with the principles of the Helsinki Declaration. The study protocol was approved by the Local Ethics Committee of these Institutes. The informed consent of the patient was obtained for conducting the studies.